Peranan pendidikan akhlak dalam menciptakan keluarga bahagia - Tarmujianto Tarmujianto (LPPM Universitas Ibn Khaldun, Bogor, 2020)
This article aims to explain how important moral education is starting from within the family where parents play a major role in educating children and are responsible for the development of their souls and beliefs. The method of writing in this article is carried out by the library research method. The method of writing in this article is carried out by the library research method. From the results of this study it can be concluded that happiness and well-being are not always related to one's success in reaching the peak or sufficient material, but can be obtained through the appreciation and practice of religious teachings. Therefore, humans are required to prepare themselves and family experts with religious education as the basic capital in carrying out life in this world and provisions for the hereafter. One of the main things is religious education which must be learned from an early age, because the teachings of Islam must be the foundation or guidance in the subsequent development of the child's soul. AbstrakArtikel ini bertujuan untuk memaparkan betapa pentingnya pendidikan akhlak yang dimulai dari dalam keluarga di mana orang tua memegang peran utama dalam mendidik anak-anak dan bertanggung jawab terhadap perkembangan jiwa dan kepercayaan mereka. Metode penulisan dalam artikel ini dilakukan dengan metode riset kepustakaan. Metode penulisan dalam artikel ini dilakukan dengan metode riset kepustakaan. Dari hasil kajian ini dapat disimpulkan bahwa kebahagiaan dan kesejahteraan tidak selalu berhubungan dengan keberhasilan seseorang dalam mencapai puncak atau materi yang tercukupi, namun dapat diperoleh melalui penghayatan dan pengamalan ajaran agamanya. Maka dari itu manusia dituntut untuk menyiapkan diri dan ahli keluarga dengan didikan agama sebagai modal dasar dalam menjalankan kehidupan di dunia dan bekal untuk di akhirat kelak. Salah satu yang utama adalah pendidikan agama yang harus dipelajari sejak dini, karena ajaran Islam harus menjadi landasan atau tuntunan dalam perkembangan jiwa anak selanjutnya.